Influence of Continuing Medical Education on Rheumatologists' Performance on National Quality Measures for Rheumatoid Arthritis. Issue 2 (December 2015) - Sapir, Tamar; Rusie, Erica; Greene, Laurence; Yazdany, Jinoos; Robbins, Mark; Ruderman, Eric; Carter, Jeffrey; Patel, Barry; Moreo, Kathleen
Abstract Introduction In recent years researchers have reported deficits in the quality of care provided to patients with rheumatoid arthritis (RA), including low rates of performance on quality measures. We sought to determine the influence of a quality improvement (QI) continuing education program on rheumatologists' performance on national quality measures for RA, along with other measures aligned with National Quality Strategy priorities. Performance was assessed through baseline and post-education chart audits. Methods Twenty community-based rheumatologists across the United States were recruited to participate in the QI education program and chart audits. Charts were retrospectively audited before (n  = 160 charts) and after (n  = 160 charts) the rheumatologists participated in a series of accredited QI-focused educational activities that included private audit feedback, small-group webinars, and online- and mobile-accessible print and video activities. The charts were audited for patient demographics and the rheumatologists' documented performance on the 6 quality measures for RA included in the Physician Quality Reporting System (PQRS). In addition, charts were abstracted for documentation of patient counseling about medication benefits/risks and adherence, lifestyle modifications, and quality of life; assessment of RA medication side effects; and assessment of RA medication adherence. Results Mean rates of documented performance on 4 of the 6 PQRS measures for RA were significantly higher in the post-education versus baseline charts (absolute increases ranged from 9 to 24% of patient charts). In addition, after the intervention, significantly higher mean rates were observed for patient counseling about medications and quality of life, and for assessments of medication side effects and adherence (absolute increases ranged from 9 to 40% of patient charts). Conclusion This pragmatic study provides preliminary evidence for the positive influence of QI-focused education in helping rheumatologists improve performance on national quality measures for RA.